Dietary (–)-epicatechin mitigates oxidative stress, NO metabolism alterations, and inflammation in renal cortex from fructose-fed rats - Prince, Paula Denise (2016)
High fructose consumption has been associated to deleterious metabolic conditions. In the kidney, high fructose causes renal alterations that contribute to the development of chronic kidney disease. Evidence suggests that dietary flavonoids have the ability to prevent/attenuate risk factors of chronic diseases. This work investigated the capacity of (–)-epicatechin to prevent the renal damage induced by high fructose consumption in rats. Male Sprague Dawley rats received 10% (w/v) fructose in the drinking water for 8 weeks, with or without supplementation with (–)-epicatechin (20 mg/kg body weight/d) in the rat chow diet. Results showed that, in the presence of mild proteinuria, the renal cortex from fructose-fed rats exhibited fibrosis and decreases in nephrin, synaptopodin, and WT1, all indicators of podocyte function in association with: (i) increased markers of oxidative stress; (ii) modifications in the determinants of NO bioavailability, i.e., NO synthase (NOS) activity and expression; and (iii) development of a pro-inflammatory condition, manifested as NF-κB activation, and associated with high expression of TNFα, iNOS, and IL-6. Dietary supplementation with (–)-epicatechin prevented or ameliorated the adverse effects of high fructose consumption. These results suggest that (–)-epicatechin ingestion would benefit when renal alterations occur associated with inflammation or metabolic diseases.